Comparative analysis of perinatal outcomes in pregnant women with pregestational diabetes mellitus based on diagnostic timing - Shu, Xinyu; Juan, Juan; Kang, Xin; Yao, Mi; Chen, Xu; Wei, Zhuo; Kong, Lingyi; Chen, Haitian; Cui, Shihong; Gao, Fengchun; Zhu, Ping; Yan, Jianying; et al. (Scientific reports, 2025)
Diabetes is a major concern in healthcare worldwide and is detrimental to mothers and fetuses during pregnancy. However, half of the women were unaware of hyperglycemia before pregnancy, and there is no consensus on their identification during pregnancy. We aim to understand the role that diagnostic timing plays in perinatal outcomes. This was a multicenter retrospective study of all pregestational diabetes mellitus (PGDM) women who delivered from January 2021 to June 2023. Diagnoses were made before or during gestation. Characteristics and outcomes were compared among stages, and logistic regression was performed to explore the relationship between adverse outcomes and the diagnostic timing. This study included 2,818 women; 1188 (42.2%) were self-aware before pregnancy, and 286 (10.1%), 1208 (42.9%), and 136 (4.8%) were diagnosed in the first, second, and third trimesters, respectively. Maternal body mass index, hypertensive disorders during pregnancy, glucose profile, large-for-gestational-age (LGA), etc., differed among stages (all P < 0.05). Logistic regression revealed that PGDM diagnosed during any trimester was significantly associated with an increased risk of macrosomia (aOR = 2.632, 1.502, 2.314; all P < 0.05). However, the risk of LGA decreased if the diagnosis was based on the 2 h value of the oral glucose tolerance test (OGTT) alone in the second trimester (aOR = 0.608, 95% CI: 0.444–0.831). No relationship existed between diagnostic timing and neonatal birth defects or hypoglycemia (both P > 0.05). PGDM identified during pregnancy was significantly associated with an increased risk of fetal overgrowth. The role of the 2 h-OGTT alone in diagnosis warrants further exploration. PGDM screening is essential for the entire gestational period.